THE ROLE OF YERBA MATE (ILEX PARAGUARIENSIS) IN THE REDISTRIBUTION OF RAINFALL BY INTERCEPTION - Santos, Ezequias Rodrigues; Vestena, Leandro Redin; Belmonte Serrato, Francisco (Ra’e Ga: o Espaço Geográfico em Análise, 2022)
Vegetation cover plays an essential role in the vertical and horizontal distribution of rainwater. As rainwater passes through the canopy, it can be divided into interception loss, throughfall, and stemflow. In the areas where yerba mate is cultivated, interception loss influences the variability of water reaching the soil, surface runoff, and nutrient cycling. The objective of this study was to evaluate throughfall, stemflow, and interception in yerba mate (Iex paraguariensis). The study was conducted in the Guará District, municipality of Guarapuava, south-central region of Paraná, Brazil. Measurements were conducted from July 2019 to March 2020. Average rainfall interception, throughfall, and stemflow for yerba mate accounted for 13.6%, 86.1%, and 0.3% of precipitation, respectively. Throughfall and stemflow increased with precipitation. The interception rate showed variation according to rainfall characteristics: volume, duration, and intensity. The structure, shape, and density of yerba mate leaves and branches result in uneven distribution of the water that reaches the soil by directing the flow to specific points. The results indicate that yerba mate caused changes in water circulation and distribution.